2019
DOI: 10.1016/j.envres.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of urinary phthalate biomarker concentrations in postmenopausal women

Abstract: Background-Phthalates are ubiquitous endocrine disrupting chemicals present in a wide variety of consumer products. However, the personal characteristics associated with phthalate exposure are unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
(57 reference statements)
2
8
0
Order By: Relevance
“…We found that urinary concentrations of the low molecular weight phthalate metabolites MEP and MBP were positively associated with BMI, which is consistent with some 40 , 59 61 but not all 62 previous studies. We also observed higher concentrations of metabolites of high molecular weight phthalates (including DINP and DEHP) among women with higher BMI.…”
Section: Discussionsupporting
confidence: 92%
“…We found that urinary concentrations of the low molecular weight phthalate metabolites MEP and MBP were positively associated with BMI, which is consistent with some 40 , 59 61 but not all 62 previous studies. We also observed higher concentrations of metabolites of high molecular weight phthalates (including DINP and DEHP) among women with higher BMI.…”
Section: Discussionsupporting
confidence: 92%
“…This could be due to the rapid biotransformation of parent compounds through metabolic processes (Staples et al., 1997), thereby preventing bioaccumulation. In humans, age‐related differences in phthalate exposure have been attributed to changes in metabolism and biotransformative properties that could potentially slow with age (Reeves et al., 2019). For example, children tend to excrete higher concentrations of oxidized DEHP metabolites (i.e., MEHHP and MEOHP) than MEHP compared to adults (Wittassek & Angerer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This large sample size enabled demographic examinations of phthalate exposure, a first for any marine mammal species. Conversely, human studies evaluating demographic differences may rely on sample sizes in the hundreds to thousands (CDC, 2019; Huang, Tsai, et al., 2015; Percy et al., 2016; Reeves et al., 2019). Second, this study relied upon well‐established CDC analytical methods to screen for phthalate metabolites in urine, a matrix that consistently yields accurate measurements, even at low concentrations (Calafat & McKee, 2006; Frederiksen et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We think smoking here may be more likely to re ect an unhealthy lifestyle. For example, the Women's Health Initiative found that a lack of healthy behaviors such as not smoking, a high-quality diet, and moderate physical activity were predictors of urinary phthalate metabolites (Reeves et al, 2019). A Norwegian study also indicated that smoking, consuming food with plastic packaging and eating with hands were associated with higher levels of phthalate metabolites (Giovanoulis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%